Control of the threading ratio of cyclic molecules in polyrotaxanes consisting of poly(ethylene glycol) and α-cyclodextrins. Issue 51 (7th June 2018) - Kobayashi, Yuichiro; Nakamitsu, Yukie; Zheng, Yongtai; Takashima, Yoshinori; Yamaguchi, Hiroyasu; Harada, Akira
Abstract : We prepared polyrotaxanes with a controlled threading ratio and chain length by extending the linear polymers in the poly-pseudorotaxane. Abstract : We demonstrated a feasible method for providing polyrotaxanes (PRxs) with a controlled threading ratio of cyclic molecules and chain length of linear polymers by extending the linear polymers in the pseudo-PRx. This method gave PRxs with a lower threading ratio and a higher mobility of cyclic molecules compared to usual methods used previously with a high threading ratio. In addition, our PRx improved the thermal stability of the linear polymers in PRx despite the low threading ratio.